Let h(t) = 6*t - 1. Let a be h(1). Suppose 0 = -3*n - f + a, -n + 7 = -0*n - 5*f. Solve 2*z + n = -0*z for z.

-1

Let s be (-1 + -2)*8/(-3). Suppose y = -3*y + 2*l + s, y = -2*l + 7. Suppose y = 3*w - 2*w. Solve 0 = 4*j + w + 1 for j.

-1

Let h = -24 - -27. Solve -h = -z - 1 for z.

2

Suppose -5*w - 24 = -o, o + 10 = -4*w - 2. Solve -o*h - 1 = -5 for h.

1

Let b© = 313 - 310 + c - 2*c. Suppose 4*n + 19 = -29. Let g be b(n). Solve -g = 2*v + v for v.

-5

Suppose -3*x - 4 = 4*w, -2*x + 3 = -4*x - 3*w. Solve 0 = -5*m - x*m + 5 for m.

1

Let u = 5 - 5. Solve 3*l + 2*l - 10 = u for l.

2

Suppose -4*j = 4*p - 4, 2*j + p - 5 = -0*p. Let d be j/(0 - (-1)/3). Let a be (-9)/d - (-57)/12. Solve 5*v - 6*v + a = 0 for v.

4

Let k = 6 - 0. Let z be 3 - (55 - 0). Solve -k = -m - z for m.

4

Let w be ((-4)/(-5))/(410). Let a be (0 + w/4)*2. Let p be 3 - (-1 + (a - 2)). Solve -5*g + p = -5 for g.

2